Les régimes de ressources au Canada : les trois crises de l'extractivisme - Yann Fournis; Marie-José Fortin (VertigO)
In Canada, the political economy of natural resources is deeply marked by the environmental crisis : more than elsewhere, the overexploitation of nature is inscribed in the very logic of Canadian capitalism. Following the studies on the production of a socio-nature, we will examine how the extractivist development model uses nature to produce a stock of ’natural resources ’. The study of the large resources regimes allows to distinguish analytically different dynamics of this production of nature, in the form of three political temporalities. On the macro-structural scale, resources regimes are the institutional legacy of a political economy historically focused on resources, which ensures the pre-eminence of international-oriented economic regulations (a staple socio-economy). On the meso-policical scale, these resources regimes are dynamic political arrangements which, while stabilizing the exploitation of resources, promotes extractivist actors to the detriment of third-party actors. On the micro-social scale, these resources regimes are finally institutional constraints to the territorial actors facing the implementation of exploitation of natural resources. Each of these temporalities bears the mark of an ecological paradox : the capitalism of resources doesn’t have much to do with the market (because of the role of large organizations), less and less to share with Canadian society (as a result of increasing disputes) and promotes the dispossession of local communities of their environment (despite recent progress). In conclusion, we will question the political significance of this type of development.